Spatial Morphology of Margorukun Village Surabaya as a Region of Local Wisdom - Iswanto, Heru Hendri; Utami, Sri; Wulandari, Lisa Dwi (University of Merdeka Malang, 2022)
Spatial morphology was formed from the land use that that was realized from a variety of activities performed in that area. Next, the building pattern and function as well as circulation pattern or road network pattern that connected between regions would also influence regional or spatial morphology. Margorukun Village was one of villages to be proud of in Surabaya. Margorukun Village has gotten award as the winner of Green and Clean Village competition program. Moreover, spatial morphology of Margorukun Village has its own uniqueness, part of village which was divided into two with different morphology. The uniqueness appeared from the local wisdom of villagers. The aim of this research was to identify how a village local wisdom could affect spatial morphology of the village. The research method in this research was descriptive qualitative. The research was conducted by performing field observation activity in form of environmental spatial element, through blueprint, layout plan, and existing image or direct observation on the research object and interview. The research result referred about how the spatial morphology of Margorukun Village and how the villager activity to build a cultural local wisdom of Margorukun Village.